2016
DOI: 10.5604/17331331.1204478
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacteria Isolation of Bacteria from Pinyon Rhizosphere, Producing Biosurfactants from Agro-Industrial Waste

Abstract: A b s t r a c tTwo hundred and fifty bacterial strains were isolated from pinyon rhizosphere and screened for biosurfactants production. Among them, six bacterial strains were selected for their potential to produce biosurfactants using two low cost wastes, crude glycerol and lactoserum, as raw material. Both wastes were useful for producing biosurfactants because of their high content in fat and carbohydrates. The six strains were identified by 16S rDNA with an identity percentage higher than 95%, three strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This activity was also higher than that of some other Enterobacter spp. such as strain SF-4 (40%) ( Batool et al 2017 ), strain LS1 (44%), strain CG101 (15%), and LS8 (50%) ( Wong-Villarreal et al 2016 ). The amount of BS obtained per gram cell dry weight was (39.8 ± 5.2) mg (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity was also higher than that of some other Enterobacter spp. such as strain SF-4 (40%) ( Batool et al 2017 ), strain LS1 (44%), strain CG101 (15%), and LS8 (50%) ( Wong-Villarreal et al 2016 ). The amount of BS obtained per gram cell dry weight was (39.8 ± 5.2) mg (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that a cell-free broth from B14 cultures can be used directly as an antimicrobial agent without purification of BS. It could significantly reduce the cost of BS production (Wong-Villarreal et al 2016). This paper aimed 3 281 to investigate emulsification activity because it is the major property that helps diminish biofilm formation by pathogens, and thus involves the antimicrobial activity of the compound.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional antibacterial materials include polyethene glycol [106], plant polyphenol [107], and biosurfactants [108]. Nowadays, nanotextured surfaces have become a relatively new field in bacteria in this complex oral environment, and they may support longstanding peri-implant health [134].…”
Section: Inhibiting Bacteriamentioning
confidence: 99%